The attractiveness of investing in the Supramax bulk carrier segment with an investment horizon from 2019 to 2023 - Wei, Xinyue (2019)
This research aims to perform a feasibility study from an institutional investor’s point of view to advice on the attractiveness of investing into Supramax sector within the timeframe from 2019 to 2013. Based on the market outlook concluded in Volume 1 by analysing the historical performance and the supply and demand factors, Volume 2 seeks to investigate the costs and returns of a Supramax ship owner and strives to find the intrinsic value of the assets. This paper begins by explaining the concepts of value creation, where returns must be able to cover costs. To measure returns, the paper decides to use Internal Rate of Return (IRR) and Net Present Value (NPV). To measure cost, the paper uses the Weight Average Cost of Capital (WACC) method and determined the cost to be 4.56%. From any investor’s perspective, the asset’s intrinsic value must be higher than the fair market value to be a profitable investment. To measure a vessel’s Intrinsic Value, the paper determines that Income Approach is the most relevant among 3 commonly used approaches, which then involves determining the Net Present Value (NPV) of the asset resulted from different employment decisions. Next, the paper determined the variables needed for the Income Approach by conducting primary researches and garnering data from secondary sources. Given the assumption that the investors will acquire a fleet of five 5-year-old Supramax bulkers, the paper creates different scenarios to find out the best acquisition-employment strategy. This paper finds that all purchasing-TC employment generated a positive IRR. For time charter, all scenarios generate positive NPV. For spot charter, a negative NPV is generated for the lowest margin of forecasted TCE band. For time-charter-in acquisition, a high TCE could generate a positive NPV. With these findings, this implies that, with the current freight band of USD$ 9,900 to USD$14,918 against the price of acquiring the assets at a given cost of running the vessel and to finance the vessel, the IV is generally higher than FMV, and thus, it is recommended for investors to invest in the Supramax segment through purchasing second-hand and time-charter out; but investor could still purchase or time-charter in the vessels and spot charter out to try their luck.